High Tide or Riptide on the Cosmic Shoreline? A Water-rich Atmosphere or Stellar Contamination for the Warm Super-Earth GJ 486b from JWST Observations - Sarah E. Moran; Kevin B. Stevenson; David K. Sing; Ryan J. MacDonald; James Kirk; Jacob Lustig-Yaeger; Sarah Peacock; L. C. Mayorga; Katherine A. Bennett; Mercedes López-Morales; E. M. May; Zafar Rustamkulov; et al. (The Astrophysical Journal Letters, 2023)
Planets orbiting M-dwarf stars are prime targets in the search for rocky exoplanet atmospheres. The small size of M dwarfs renders their planets exceptional targets for transmission spectroscopy, facilitating atmospheric characterization. However, it remains unknown whether their host stars’ highly variable extreme-UV radiation environments allow atmospheres to persist. With JWST, we have begun to determine whether or not the most favorable rocky worlds orbiting M dwarfs have detectable atmospheres. Here, we present a 2.8–5.2 μ m JWST NIRSpec/G395H transmission spectrum of the warm (700 K, 40.3× Earth’s insolation) super-Earth GJ 486b (1.3 R _⊕ and 3.0 M _⊕ ). The measured spectrum from our two transits of GJ 486b deviates from a flat line at 2.2 σ − 3.3 σ , based on three independent reductions. Through a combination of forward and retrieval models, we determine that GJ 486b either has a water-rich atmosphere (with the most stringent constraint on the retrieved water abundance of H _2 O > 10% to 2 σ ) or the transmission spectrum is contaminated by water present in cool unocculted starspots. We also find that the measured stellar spectrum is best fit by a stellar model with cool starspots and hot faculae. While both retrieval scenarios provide equal quality fits ( ${χ }_{ν }^{2}=1.0$ ) to our NIRSpec/G395H observations, shorter wavelength observations can break this degeneracy and reveal if GJ 486b sustains a water-rich atmosphere.